Health and safety implementation motivators in the South African construction industry. Issue 1 (1st January 2018) - van Heerden, Jacobus H.F.; Musonda, Innocent; Okoro, Chioma S.
Abstract: The increased emphasis on health and safety (H&S) in the construction industry in recent years necessitates continuous research on strategies to improve H&S performance in the sector. However, the motives behind the implementation of H&S practices in the construction industry has been explored to a limited extent. The aim of the current study is to classify the drivers behind H&S implementation in the South African construction industry. A field survey was undertaken. Participants, selected through judgemental and snowball sampling techniques, included site engineers, site agents, contracts managers, construction managers and project managers. Mean item score and standard deviation were determined using EXCEL. The need to manage hazards; organisations regard H&S as important; and compliance with the legislation emerged as the most important drivers. The study provides evidence for construction organisations to develop effective strategies to mitigate the occurrence of fatalities and deaths in the construction industry. More robust data analysis techniques could be employed in further studies.